The association between home modifications and depression among older people in China - Xuanru Lyu; Jian Sun; Jian Sun (Frontiers in Public Health)
BackgroundAs individuals age, their living environments often become inadequate to meet the evolving demands associated with aging. An accommodating home environment is crucial for ensuring the health and well-being of older people. Home modifications effectively create a supportive living space for those who choose to age in place. The objective of the study is to examine the association between home modifications and the depression levels of older people in China.MethodsUsing data from 5,706 urban older people collected in the 2018 China Longitudinal Aging Social Survey (CLASS), this study employs a multivariate ordered logistic regression model and propensity score matching (PSM) to assess the association between home modifications and depression levels among older people in China.ResultsThe results suggest that home modifications are significantly associated with a reduction in depression among older people, with a greater degree of modification correlating with more substantial reductions in depressive symptoms. These findings remained consistent across various models and robustness checks, suggesting that modifying the living environment can significantly benefit older people’ mental health.ConclusionThese findings demonstrate the significance of the implementation of home modifications as a practical intervention for improving mental health by reducing depression levels among older people in China.